Réponses

2013-05-11T19:14:30+02:00
J) tu places tout les x d'un coté et les chiffres de l'autre :
5x+6x=7+3
11x=10
x=10/11

k) -3x-6x=4-7
-9x=-3
x=-3/-9
x=1/3

l) 4x-5x=-6-9
-x=-15
x=15

m) 6x-8x=9+5
-2x=14
x=14/-2
x=-7

n) 4x+3x-8x=6-4-4
-x=-2
x=2

o) 6x+7x-8x-3x=3-6+7
2x=4
x=4/2
x=2
Meilleure réponse !
  • Utilisateur Brainly
2013-05-11T19:20:29+02:00

j)

5x-3=6x+7

5x-3-6x=6x+7-6x

-1x-3=7

-1x-3+3=7+3

-1x=10

x=10/-1

x=-10

 

k)

7-3x=6x+4

7-3x-6x=6x+4-6x

7-9x=4

7-9x-7=4-7

-9x=-3

x=-3/-9

 

l)

4x+6=5x-9

4x+6-5x=5x-9-5x

-1x+6=-9

-1x+6-6=-9-6

-1x=-15

x=-15/-1

x=-15

 

m)

6x-5=8x+9

6x-5-8x=8x+9-8x

-2x-5=+9

-2x-5+5=9+5

-2x=14

x=14/-2

x=-7

 

n)

4x+4+3x=6+8x-4

7x+4=6+8x-4

7x+4-8x=6+8x-4+8x

-1x+4=6-4

-1x+4=2

-1x+4-4=2-4

-1x=-2

x=-2/-1

x=-2

 

o)

6x-3+7x=8x-6+3x+7

13x-3=11x-6+7

13x-3-11x=11x-6+7-11x

2x-3=-6+7

2x-3=1

2x-3+3=1+3

2x=4

x=4/2

x=2

 

voilà........ :)